2002
DOI: 10.1139/g02-058
|View full text |Cite
|
Sign up to set email alerts
|

Tandem repeats and length variation in the mitochondrial DNA control region ofEpirrita autumnata(Lepidoptera: Geometridae)

Abstract: The organization of the mitochondrial DNA (mtDNA) control region (CR) of the autumnal moth, Epirrita autumnata, is described. The E. autumnata CR presents a distinct type of lepidopteran CR with domains of non-repetitive and repetitive sequences. The CRs show considerable length variation owing to a variable number of short approximately 29-bp sequence blocks that are repeated between 6 and 14 times in tandem. The organization of such a tandem array is unique among the insect CRs examined so far. Furthermore, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 17 publications
1
10
0
Order By: Relevance
“…This has also been reported in studies of other flies (Lessinger and Azeredo-Espin, 2000) and even other insects (Zhang et al, 1995;Snall et al, 2002;Saitou et al, 2005). T-stretches are thought to be a conserved motif among insects and are most likely associated with some function of mtDNA.…”
Section: Conserved Motif In the Type I Element And Its Downstream Regionsupporting
confidence: 69%
See 1 more Smart Citation
“…This has also been reported in studies of other flies (Lessinger and Azeredo-Espin, 2000) and even other insects (Zhang et al, 1995;Snall et al, 2002;Saitou et al, 2005). T-stretches are thought to be a conserved motif among insects and are most likely associated with some function of mtDNA.…”
Section: Conserved Motif In the Type I Element And Its Downstream Regionsupporting
confidence: 69%
“…In insects, the control region contains nearly 90% adenine (A) and thymine (T), and thus is referred to as an A+T-rich region. This region has been analyzed in crickets (Rand and Harrison, 1989), honeybees (Crozier and Crozier, 1993), grasshoppers (Zhang et al, 1995), moths (Snall et al, 2002), mosquitoes (Caccone et al, 1996), and flies (Clary and Wolstenholme, 1985;Monnerot et al, 1990;Monforte et al, 1993;Lewis et al, 1994;Brehm et al, 2001), as well as in other insects. These previous studies have identified the sequence of the Ts (T-stretch) and the putative secondary structures in the A+T-rich region.…”
Section: Introductionmentioning
confidence: 99%
“…The variable number tandem repeats (VNTRs) of the mtDNA noncoding region have been previously described for fishes (Arnason and Rand 1992;Broughton and Dowling 1994;Cesaroni et al 1997;Nesbo et al 1998;Ludwig et al 2000;Mjelle et al 2008), rabbits (Casane et al 1994), bats (Wilkinson and Chapman 1991;Wilkinson et al 1997;Petri et al 1996), hornbills (Delport et al 2002), rodents (Larizza et al 2001), large cats (Kim et al 2001), mammalians (Sbisa et al 1997), the autumnal moth (Snall et al 2002), crocodilians (Ray and Densmore 2003), marsupials (Nilsson 2009), and humans (Walberg and Clayton 1981;Soong et al 1997;Lutz et al 1999). Studies involving mtDNA VNTRs at the population level have shown variations ranging from a combination of little substructure (Arnason and Rand 1992;Broughton and Dowling 1994) to population differentiation (Cesaroni et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Although the D. saccharalis mtDNA CR size was similar to the one described for most Lepidoptera (Taylor et al, 1993), it was the shortest among the control regions analyzed in this study. The length variation and stretches of the repetitive and nonrepetitive sequences in the Lepidoptera mtDNA CR were described for Epirrita autumnata, which presented an mtDNA CR with 1075 bp (Snall et al, 2002). The mtDNA CR from B. mandarina (Japanese) presented 746 bp, B. mori 498 bp, B. mandarina (Chinese) 483 bp, C. pomonella 432 bp and D. saccharalis 338 bp, Fig.…”
Section: Resultsmentioning
confidence: 92%